A STUDY OF ALTERNATIVE LOCAL FOOD SOURCES IN JAMBI PROVINCE - Dompak Napitupulu; Saad Murdy (Socio-Economics/Agribusiness Department, 2016)
Rice is a major staple food commodity in Indonesia. It plays important role both as socio-politic and economic commodity. Rice should be available in sufficient amount to all markets; otherwise economic and politic stability well not run well. In order to fulfill the needs, it should be imported from other countries. This research was conducted to find out alternative local food sources in order to substitute rice commodity as energy and carbohydrate source in Jambi Province. This research was conducted in 2011 and located in four regencies of Jambi Province. The research result showed that 100% research respondents stated that rice still became main staple food as energy and carbohydrate source where they usually eat rice three times a day. In addition, other staple foods that consumed by Jambi people as energy and carbohydrate source were potato, cassava, sweet potato and soybean. There was rarely respondents, or none, that have consumed corn, sago, achira (or canna discolor), breadfruit and arrowroot as their staple food although those kinds of local foods were available around them.